The Study of Annual Health Examination Result by Using Testing Fuzzy Hypotheses with Fuzzy P-Value - Vonglao, Paothai (Asian Health, Science and Technology Reports, 2018)
The research aimed to study a health evaluation method from the annual health examination by an application of testing fuzzy hypotheses. The fuzzy p-value is used for the testing. The reason that we need to apply the fuzzy hypotheses testing, because classical hypotheses testing can not test the difference between a population mean with an interval of constant. The participants were 136 recipients who had an annual health examination in Ubon Rachathani Rajabhat University in 2015. Research instrument was the simplified forms with result recorded from a laboratory examination in an annual health examination. Statistics used in data analysis were testing fuzzy hypotheses by using fuzzy p-value and percentage. The method of health diagnosis was the testing fuzzy hypotheses by using fuzzy p-value consisted of the followings : 1) Set the fuzzy hypotheses to insist the results from laboratory in the annual health examination. 2) Set fuzzy significant level. 3) Define the test statistic. 4) Finding the fuzzy p-value. 5) Compare the fuzzy p-value with the fuzzy significant and 6) Make decision. Most of the results from laboratory in annual health examination were in normal value with degree 0.8627-1.0. The study indicated that the values of cholesterol was higher than normal value with degree 1.